Combined Effect of Chitosan Coating and Laurel Essential Oil (Laurus nobilis) on the Microbiological, Chemical, and Sensory Attributes of Water Buffalo Meat - Lydia K. Karakosta; Kornilia A. Vatavali; Ioanna S. Kosma; Anastasia V. Badeka; Michael G. Kontominas (Foods, 2022)
The combined effect of chitosan coating (CHI) and laurel essential oil (LEO) on the shelf-life extension of water buffalo meat stored under aerobic packaging conditions at 4 °C was investigated. Microbiological, physicochemical, and sensory attributes were monitored over an 18-day storage period. Microbiological data indicated that the (CHI) coating along with (LEO) was the most efficient among treatments in reducing populations of bacteria by 3.2 log cfu/g on day 6 of storage (p < 0.05). pH values of meat varied between 6.04 and 6.21, while thiobarbituric acid (TBA) values were equal to or less than 2.12 mg malondialdehyde/kg throughout storage. The colour parameter L* and a* values decreased, while b* values increased during storage (p < 0.05). Taste proved to be a more sensitive sensory attribute than odour. Based on sensory and microbiological data, product shelf life was approximately 5–6 days for control samples, 7–8 days for samples treated with (LEO), 12 days for samples treated with (CHI), and 13–14 days for samples treated with (CHI + LEO).